Pengaruh faktor tekanan dan ukuran perusahaan terhadap kecurangan laporan keuangan - Siswantoro Siswantoro (Penerbit Goodwood, 2020)
Purpose: The purpose’s study was to understand whether the three factors of pressure (financial stability, financial target and external pressure) and company size can influence financial statement fraud. Research methodology: The data analysis method used logistic regression analysis, and the analysis tool is SPSS v21. The population in this study were 40 banking companies listed on the IDX with a research time of 3 years, from 2017-2019. The total sample was 99 samples. Results: One of the three pressure factors, namely financial targets, had a positive and significant effect on fraudulent financial statements, while financial stability and external pressure had no positive and significant effect. Company size is not able to influence financial statement fraud. Limitations: This research used only four independent variables and the pressure factor dimensions of fraud theory to predict that effect on fraudulent financial statements and only examines one object, namely banking companies. The period of the study is relatively short, only three years. Contribution: The results of this study are useful for principals to be more selective in choosing companies to invest in. Keywords: Fraudulent financial statements, Financial stability, Financial target, External pressure, Company size